The adaptive value of secondary males in the polygynous multi‐level society of hamadryas baboons. Issue 3 (14th July 2015) - Chowdhury, Shahrina; Pines, Mathew; Saunders, Julian; Swedell, Larissa
ABSTRACT Objectives One‐male social systems are usually characterized by polygyny and reproductive exclusion by a single resident male. Sometimes, however, secondary males join these groups, and this may carry fitness costs and/or benefits to the resident male. In hamadryas baboons (Papio hamadryas hamadryas), which live in one‐male units (OMUs) with female defense polygyny within a multi‐level social system, secondary "follower" males often reside in OMUs. Our aim here is to examine possible benefits of these secondary males to hamadryas resident males. Materials and Methods Using 6 years of data from 65 OMUs in a band of wild hamadryas baboons in Ethiopia, we compared demographic and reproductive parameters of OMUs with and without secondary "follower" males to assess whether their presence conferred any reproductive benefits to resident "leader" males. Results Leaders with followers had tenure lengths almost twice as long, acquired more than twice as many females, retained females longer, and had three times as many infants during their tenure compared to leaders without followers. Discussion Hamadryas follower males enabled leaders to retain females for longer periods of time—likely through unit defense, social relationships with OMU members, and/or infant protection. Hamadryas leaders appear to be able to monopolize access to females despite the presence of followers, and as such any enhanced reproduction derived from the presence of followers likely increases the fitness of the leader rather than the follower. Thus the relationship between leaders and followers in hamadryas society appears to be a mutually beneficial one and tolerance of secondary males may be an adaptive reproductive strategy characterizing hamadryas leader males. Am J Phys Anthropol 158:501–513, 2015. © 2015 Wiley Periodicals, Inc.